1992
DOI: 10.1093/jn/122.8.1620
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Selenium Stabilizes Glutathione Peroxidase mRNA in Rat Liver

Abstract: The objective of these studies was to determine the step at which dietary selenium (Se) regulates the pre-translational expression of the gene for cytosolic Se-glutathione peroxidase (Se-GPX) in rat liver. Weanling male Sprague-Dawley rats were fed a Torula yeast-based Se-deficient diet, or the same diet supplemented with 0.5 mg/kg as Na2SeO3, for at least 40 d. Livers were excised and divided into three portions for isolation of nuclei, for purification of total RNA and for assay of Se-GPX activity. Nuclei we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…In the present study, Se-deficient GPX1 mRNA levels were 10 to 15% of Se-adequate levels, similar to previous reports. 14,16,17 This 85 to 90% decrease in GPX1 mRNA level was observed using Northern blot analysis for samples with equal amounts of total RNA and by slot-blot analysis for samples with equal amounts of mRNA. Dietary Se status had no effect on poly A mRNA levels or on β-actin mRNA levels, further demonstrating that the mechanism for Se regulation of GPX1 mRNA is specific.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the present study, Se-deficient GPX1 mRNA levels were 10 to 15% of Se-adequate levels, similar to previous reports. 14,16,17 This 85 to 90% decrease in GPX1 mRNA level was observed using Northern blot analysis for samples with equal amounts of total RNA and by slot-blot analysis for samples with equal amounts of mRNA. Dietary Se status had no effect on poly A mRNA levels or on β-actin mRNA levels, further demonstrating that the mechanism for Se regulation of GPX1 mRNA is specific.…”
Section: Discussionmentioning
confidence: 81%
“…In rats fed a Sedeficient diet, liver GPX1 mRNA levels decrease exponentially to approximately 10% of Se-adequate levels. 2,6,[14][15][16][17] Several studies have shown that GPX1 transcription is not affected by Se status, [17][18][19] indicating that Se status must regulate GPX1 mRNA stability. We have recently demonstrated that the GPX1 3' untranslated region (3'UTR) is necessary for GPX1 mRNA levels to decrease in Se-deficient cells, 20 suggesting that the GPX1 3'UTR may contain an Se-responsive element.…”
Section: Introductionmentioning
confidence: 99%
“…Some elevation may arise from increased transcription since for all selenazolidines except 2-methylSCA, the magnitude of the increase was significantly diminished in the presence of actinomycin D. That some elevation was still evident would suggest that additional mechanisms are operating, however, possibly mRNA stabilization. Such a mechanism has been implicated in maintaining hepatic glutathione peroxidase mRNA levels in a selenium-sufficient as compared to a selenium-deficient diet in rats (Christensen and Burgener, 1992). The elevation seen in the Ugt1a6 transcript with cycloheximide present provides evidence of additional unusual features in the regulation of this gene; in this case, the possibility of the presence of an inhibitory transcription factor.…”
Section: Discussionmentioning
confidence: 88%
“…Gene expression and translational efficiency are upregulated by selenium. 41 Dietary selenium stabilizes GPx mRNA 42 and the 3Ј untranslated region of the GPx gene plays an important role in GPx gene expression. 43 Enzyme activity of GPx is also upregulated by selenium in human cell lines.…”
Section: Effect Of Genistein On Antioxidant Enzymes Activities In Lncmentioning
confidence: 99%